Evaluating financial performance: ratio analysis and common-size financial statement analysis. A case Metrology Corporation Malaysia Sendirian Berhad / Mohamad Hairizal Harun - Harun, Mohamad Hairizal (Faculty of Business and Management, 2011)
Metrology Corporation Malaysia Sdn Bhd was incorporated with the sole objective of providing the verification and re-verification services for all weighing and all measuring instruments use for trade in Malaysia. The company started operation on the 4th April, 2005. Before that all the weighing and measuring instruments were verified and re-verified by the Metric Unit, Enforcement Division, Ministry of Domestic Trade And Consumer Affair. This project paper will focus on how this firm performance during 4 years ago. Start from 2007 until 2010. This project paper will calculate the ratio analysis of this firm that been extract from income statement and balance sheet. To concrete this ratio, the researcher also includes a common size analysis as the side evidence about this company financial performance. The purpose of this analysis, to compare how the company performance throughout from 2007 until 2010. Data are being collected by interview, journal. Thus further studied being done to show how the financial position about this firm.The result indicates that, the used of these method contribute to the reasons and evidence that based on the trend of the financial statements.